Association of Myopia in Elementary School Students in Jiaojiang District, Taizhou City, China - Xin Lu; Congcong Guo; Bin Xu; Chenwei Hou; Xiaoming Huang; Hui Xu; Zhichun Weng (Journal of Ophthalmology)
Background. The aim of our study was to evaluate the prevalence of myopia in elementary school students and to assess the risk factors for myopia. Methods. This school-based cross-sectional study was performed on students from two elementary schools in Jiaojiang, Taizhou City, China. A total of 556 students, whose age ranged from 9 to 12 years, were included. The uncorrected visual acuity and noncycloplegic refractive error tests were performed to determine the myopia. Each student was asked to fulfill the questionnaire about the possible factors associated with myopia. Multivariate logistic analyses of risk factors were conducted. Results. The overall prevalence of myopia among those students was 63.7%, ranged from 53.4% in grade 4 to 72.5% in grade 6. Multivariate logistic analysis showed that adjusting the height of desks and chairs according to the changing height and the presence of myopia in parents were significantly associated with myopia in these students, respectively. Conclusions. Our results showed that myopia among elementary school students was associated with environmental and hereditary factors.